Plastic eta factor and blunting line for characterization of fracture toughness of dissimilar metal weld. Issue 5 (7th March 2019) - Kumar, Suranjit; Kumar, Anshu; Singh, Pawan Kumar; Chattopadhyay, Jayanta
Abstract: This paper addresses the fracture toughness evaluation procedure of different zones of dissimilar metal weld (DMW). Experiments have been conducted on compact tension specimens from DMW joint having initial notch in centre of weld and fusion boundaries. Plastic eta factors ( η p ) and slope of blunting line ( bl ) for above specimens have been evaluated numerically. Experimental load, load line displacement, and crack growth data along with numerically evaluated η p and bl have been used for calculation of fracture resistance curve and initiation fracture toughness, and finally, it has been compared with that evaluated as per ASTM E1820 and ESIS standard.